PENGARUH KONDISI EKONOMI KELUARGA TERHADAP MOTVASI MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA SISWA KELAS XII SMA SERI RAMA YLPI PEKANBARU - Fitriyani, Rahma Fitriyani Rahma; Nas, Syakdanur Nas Syakdanur; ', Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aimed to determine the effect of economic conditions of families on the motivation to continue their education to college in high school class XII students Seri Rama YLPI Pekanbaru. This research was conducted at SMA Series Rama YLPI Pekanbaru from October to December 2014. The research method used is descriptive quantitative method. Population of 145 people and a sample of 60 people is the student and the student's family. Data collection instrument was a questionnaire with Likert scale for the dependent variable: Motivation Continuing Education (Y); independent variables: Family Economic Conditions (X). The data analysis technique used is a statistical technique with simple linear regression. From the results, it can be concluded that: (1) family economic conditions affect the motivation to continue their education to college (2) the effect of the economic conditions of families on the motivation to continue their education to college in high school class XII students Seri Rama YLPI Pekanbaru at 44.89%. Keywords : Family economic conditions, motivation